Odpowiedź :
A. 2x+6=5+3x
2x-3x=5-6
-x=-1
x=1
B. 2x-3=2+4x
2x-4x=2+3
-2x=5
x=-5/2
C. x+2+3(x-1)=9
x+2+3x-3=9
4x-1=9
4x=10
x=5/2
D. 3(2x+3)=5(2-x)+15x
6x+9=10-5x+15x
6x+9=10+10x
6x-10x=10-9
-4x=1
x=-1/4
Odpowiedź:
a) x=1 b)x= -(5/2) c)x=5/2 d)x=1/4
Szczegółowe wyjaśnienie:
a) x/3 + 1 + 5/6 + x/2 //×6
2x+6=5+3x
2x-3x=5-6
-x=-1
x=1
b)
(2x-3)/4=1/2+x //×4
2x-3=2+4x
2x-4x=2+3
-2x=5//÷(-2)
x= -(5/2)
c)
(x+2)/9 + (x-1)/3 = 1 //×9
(x+2) + (3x-3) = 9
x + 2 +3x - 3 = 9
4x = 9-2+3
4x=10 //÷4
x=5/2
d)
(2x+3)/5 = (2-x)/3 + x //×15
6x+9=10-5x+15x
6x-10x=10-9
-4x=1//÷10
x=1/4
Liczę na naj